2002
DOI: 10.1111/j.1572-0241.2002.05788.x
|View full text |Cite
|
Sign up to set email alerts
|

Current liver biopsy practices for suspected parenchymal liver diseases in the United States: the evolving role of radiologists

Abstract: Respondents' chief concern was patient safety, and most used US for this reason. Private practitioners were less likely than those practicing in academic centers to use US guidance and were more likely to refer patients to Radiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…Our results demonstrate a continuous increase in the proportion of liver biopsies being performed under realtime US-guidance since 1997. This trend is consistent with other studies which show a shift towards liver biopsies being performed under US guidance by either gastroenterologists or radiologists [9,10]. Muir and colleagues, in 2002, reported that nearly half of surveyed gastroenterologists had their patients' liver biopsies performed under US-guidance.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Our results demonstrate a continuous increase in the proportion of liver biopsies being performed under realtime US-guidance since 1997. This trend is consistent with other studies which show a shift towards liver biopsies being performed under US guidance by either gastroenterologists or radiologists [9,10]. Muir and colleagues, in 2002, reported that nearly half of surveyed gastroenterologists had their patients' liver biopsies performed under US-guidance.…”
Section: Discussionsupporting
confidence: 85%
“…Seventy-six percent of the respondents used US-guidance to perform liver biopsies; of these 75% reported patient safety as a reason for using US-guidance, and 77% felt that it was unnecessary to perform unguided biopsies. Another reported reason for referral to a radiologist in this survey included a desire for real time ultrasound [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent US survey, 76% of 260 randomly selected members of the American Association for the Study of Liver Diseases (AASLD) reported using ultrasound guidance during liver biopsy, primarily for patient safety; 62% relied on an ultrasonographer to locate and mark the biopsy site; and 18% had the biopsy performed by the radiologist under real-time ultrasound guidance [48]. Members of the Duke University Digestive Epidemiological Studies Consortium were also surveyed; 29.5% of these physicians stated that they did not perform liver biopsies themselves but referred patients to radiologists.…”
Section: Technical Considerationsmentioning
confidence: 99%